2021
DOI: 10.3389/fpls.2021.685416
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Responses of Ripe Cherry Tomato Fruit Exposed to Chilling and Rewarming Identify Reversible and Irreversible Gene Expression Changes

Abstract: Tomato fruit stored below 12°C lose quality and can develop chilling injury upon subsequent transfer to a shelf temperature of 20°C. The more severe symptoms of altered fruit softening, uneven ripening and susceptibility to rots can cause postharvest losses. We compared the effects of exposure to mild (10°C) and severe chilling (4°C) on the fruit quality and transcriptome of ‘Angelle’, a cherry-type tomato, harvested at the red ripe stage. Storage at 4°C (but not at 10°C) for 27 days plus an additional 6 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…SlDCL2s have been widely studied in terms of plant defense against viral pathogens (Wang et al, 2018;Suzuki et al, 2019;Alcaide et al, 2022). Hunter et al (2021) also demonstrated that transcripts of both SlDCL2b and SlDCL2d accumulated to a great degree in ripe cherry tomato fruits during cold storage, but our present study is the first to show that this accumulation is unique to cold stress and is independent of ethylene signaling. Treatment of mature green tomato fruit with the DNA methylation inhibitor, 5azacytidine, confirmed the existence of cold stress-induced methylation dynamics and its influence on gene expression (Figure 9).…”
Section: Discussionsupporting
confidence: 44%
“…SlDCL2s have been widely studied in terms of plant defense against viral pathogens (Wang et al, 2018;Suzuki et al, 2019;Alcaide et al, 2022). Hunter et al (2021) also demonstrated that transcripts of both SlDCL2b and SlDCL2d accumulated to a great degree in ripe cherry tomato fruits during cold storage, but our present study is the first to show that this accumulation is unique to cold stress and is independent of ethylene signaling. Treatment of mature green tomato fruit with the DNA methylation inhibitor, 5azacytidine, confirmed the existence of cold stress-induced methylation dynamics and its influence on gene expression (Figure 9).…”
Section: Discussionsupporting
confidence: 44%
“…The highly important TFs, including MYBs and bHLH, are instrumental in the biosynthesis and homeostasis of flavonoids [29,30]. Our data unveiled that 182 differentially expressed TFs (DETFs) from 37 TF families were discovered in the RP sweet cherries and this percentage is shown in Figure 4.…”
Section: Tfs Are Relevant To Differential Accumulation Of Metabolites...mentioning
confidence: 72%
“…Through the use of correlation and clustering analyses, transcript and metabolite datasets have been combined and can be visualized as connection networks between genes and metabolites [27]. These networks can show the response mechanism of rice to high nighttime temperatures [28], the regulation mechanism of delphinidin in flower color in grape hyacinths [29], the mechanism of potato pigmentation [30], the mechanism of blue flower formation in waterlilies [31], and catechin production in albino tea. The merging of transcriptomics and metabolomics offers substantial benefits for uncovering the biosynthetic mechanisms of important metabolic pathways [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The lower UA content of the WSP extract (Figure 1A), the accompanying higher UA content in the insoluble cell wall residue (Figure 1B), the absent increase in molecular weight of WSP characteristics for apricots ripening at 20 • C to similar firmness (Figure 2B), as well as the UA content of NSP remaining similar to that of fruit at harvest instead of decreasing (Figure 1C), all indicate that 'normal' softening events were already altered during softening in cold storage and were not resumed after taking fruit out of cold storage. In tomato, although not a stonefruit, it has been shown that most cell wall enzymes do not recover expression after cold storage when returned to shelf temperature of 20 • C [25].…”
Section: Discussionmentioning
confidence: 99%